Chitin extraction from house crickets (acheta domesticus) using a green method with sonication heating - Shakila, Tasya Nur; Sonia, Gita; Anjani, Cindy Salsabilla; Pambudi, Teguh; Umam, Hilman Imadul; Fauzie, Azis Kemal; Putri, Fajar Amelia Rachmawati (Sainteks: Jurnal Sain dan Teknik, 2025)
Chitin extraction from house crickets (Acheta domesticus) has been optimized by combining a green method using Deep Eutectic Solvent (DES) and sonication heating, thereby reducing environmental impact and improving time efficiency. The extraction process consisted of insect preparation, delipidation, demineralization, and deproteinization. The results show that the green process method with DES and sonication heating is effective in enhancing time efficiency, reducing mineral content by 56.52%, decreasing protein content by 84.94%, and increasing the degree of acetylation by 21%. However, there was a slight difference in the deproteinization results when compared to the cricket samples treated with reflux. FTIR analysis confirmed the purity and structural characteristics of the extracted chitin